Early weight loss is an independent risk factor for shorter survival and increased side effects in patients with metastatic colorectal cancer undergoing first‐line treatment within the randomized Phase III trial FIRE‐3 (AIO KRK‐0306). Issue 1 (6th September 2021) - Liu, Lian; Erickson, Nicole Tonya; Ricard, Ingrid; von Weikersthal, Ludwig Fischer; Lerch, Markus M.; Decker, Thomas; Kiani, Alexander; Kaiser, Florian; Heintges, Tobias; Kahl, Christoph; Kullmann, Frank; Scheithauer, Werner; et al.
Abstract: Body weight loss is frequently regarded as negatively related to outcomes in patients with malignancies. This retrospective analysis of the FIRE‐3 study evaluated the evolution of body weight in patients with metastatic colorectal cancer (mCRC). FIRE‐3 evaluated first‐line FOLFIRI (folinic acid, fluorouracil and irinotecan) plus cetuximab or bevacizumab in mCRC patients with RAS ‐WT tumors (ie, wild‐type in KRAS and NRAS exons 2‐4). The prognostic and predictive relevance of early weight loss (EWL) regarding patient outcomes and treatment side effects were evaluated. Retrospective data on body weight during first 6 months of treatment were evaluated (N = 326). To correlate with efficacy endpoints and treatment side effects, patients were grouped according to clinically significant EWL ≥5% and <5% at Month 3. Age constituted the only significant predictor of EWL following a linear relationship with the corresponding log odds ratio ( P  = .016). EWL was significantly associated with the incident frequencies of diarrhea, edema, fatigue, nausea and vomiting. Further, a multivariate analysis revealed EWL to be an independent negative prognostic factor for overall survival (32.4 vs 21.1 months; hazard ratio [HR]: 1.64; 95% confidence interval [CI] = 1.13‐2.38; P  = .0098) and progression‐free survival (11.8 vs 9.0 months; HR: 1.72; 95% CI = 1.18‐2.5; P  = .0048). In conclusion, EWL during systemic treatment against mCRC is significantly associated with patient age. Patients exhibiting EWL had worse survival and higher frequencies of adverse events. Early preventative measures targeted at weight maintenance should be evaluated, especially in elderly patients being at highest risk of EWL. Abstract : What's new? When patients with metastatic colorectal cancer (mCRC) rapidly lose weight early in the course of treatment, that often forebodes a negative outcome. Here, the authors examined changes in body weight in the first 3 months of treatment. Older patients had the highest risk of extreme early weight loss (greater than 5%). This weight loss was correlated with adverse events such as nausea, vomiting, and diarrhoea, and also with an 11‐month reduction in overall survival. These results should increase oncologists' awareness of patients' body weight change early in treatment and encourage intervention from dietitians to help prevent weight loss.